TINJAUAN FATWA DSN-MUI NOMOR 77 DSN/MUI/V/2010 TENTANG JUAL BELI EMAS SECARA TIDAK TUNAI TERHADAP ARISAN EMAS DI PEGADAIAN SYARIAH: (Studi Kasus Arisan Emas di Pegadaian Syariah Cinere Raya, Jakarta Selatan) - Amirah Nahrawi; Nuraini (JURNAL ILMIAH NUSANTARA, 2026)
The development of Islamic financial products in Indonesia has generated various innovations, one of which is the gold rotating savings scheme (arisan emas) administered by Pegadaian Syariah Cinere. This product integrates a collective rotating savings mechanism with gradual gold ownership through an installment system. This study aims to analyze the contractual structure applied in the gold arisan scheme and to assess its compliance with the Fatwa of the Dewan Syariah Nasional Majelis Ulama Indonesia Number 77/DSN-MUI/V/2010 concerning non-cash gold transactions. This research employs a qualitative method with an empirical legal approach using a case study design. Data were collected through interviews, direct observation, and documentation, with in-depth interviews conducted with the branch manager as the primary informant. The findings indicate the following. First, the gold arisan scheme applies solely a rahn (pledge) contract, initiated by the down payment and the signing of the agreement by the group leader. The scheme operates for a six-month period, and the group leader assumes responsibility if any participant withdraws. Second, the implementation of the gold arisan does not fully conform to Fatwa Number 77/DSN-MUI/V/2010 on non-cash gold transactions, although general procedural requirements such as application through the Islamic pawnshop institution and a minimum of six participants are fulfilled.